Therapeutic dentistry in prehistoric Maryland—New analyses from the Hughes (18MO1) archeological site. (13th July 2022) - Nase, John B.; Kollmann, Dana D.; Dikin, Dmitriy A.; Montoya, Carolina
Abstract: Late Woodland period prehistoric human remains recovered from the Hughes site (18MO1) in the 1930s were only recently submitted for bioarcheological analysis. These remains represent 20 individuals exhibiting varying degrees of preservation and representation. Among the remains are several teeth suspected of undergoing antemortem dental modification. All of the examined dental cavitations were deep, and some show excavation all the way to the pulp. Dental remains representing three individuals (two adult females and a child) were examined to define etiology of altered occlusal cavitations in these teeth. The findings provide evidence of prehistoric, therapeutic dentistry in the Middle Atlantic region of the eastern United States. Two mandibles and a maxillary right dental quadrant representing three individuals were analyzed utilizing radiographs, visible and alternate light source macro photography, and scanning electron microscopy in three modes of detection. All three specimens showed signs of both radial and concentric tool marks to varying degrees in both enamel and dentin borders of carious lesions. The shape of the cavitations do not follow normal pathological patterns of undisturbed occlusal decay in teeth. Further, evidence is presented that the excavative tool motion changes from rotational drilling to radial scooping the further posterior the cavitation is located in the oral cavity. Lastly, it is proposed that the reason for these modifications was therapeutic dentistry.